3D numerical model of the creep response of hot mix asphalt prepared with capsules containing waste oil - Ozdemir, Ahmet Munir; Yalcin, Erkut; Yilmaz, Mehmet; Kok, Baha Vural; Cambay, Ertugrul (Taylor & Francis Inc, 2024)
The most widely used method in the self-healing of hot mix asphalt is the capsule method. In this method, the capsules effect the mechanical properties of asphalt mixtures. In order to determine the effect of capsules on the mechanical properties of asphalt mixtures, capsules containing waste vegetable oil in four different ratios (0.25%; 0.50%; 0.75% and 1.00%) were added to the mixtures. The mechanical properties of asphalt mixtures with and without capsules were determined by applying the creep test at single stress (450 kPa). Thanks to these test results, after the capsules written in 4 different ratios were randomly distributed into the sample with Python code, the creep test was carried out under three different constant stresses (300, 450 and 600 kPa) using the finite element method. Finally, the Response Surface Method (RSM) analysis was carried out to evaluate the relationship between variables and permanent deformations, thus it was aimed to gain a statistical perspective to the study. As a result of the simulation, differences caused by the capsules were observed. Accordingly, it was determined that the addition of capsules increased the permanent deformation rate of asphalt mixtures. As a result of the RSM analysis, it is seen that the model performs the analysis with high accuracy.
Keywords: 3D model; asphalt mixture; encapsulated rejuvenators; numerical simulation; response surface method